Responsibility of the Indonesia Deposit Insurance Corporation in Protecting Customer Funds Due to Bank Failure - Aminullah Aminullah (JUPE : Jurnal Pendidikan Mandala, 2026)
The Indonesia Deposit Insurance Corporation (Lembaga Penjamin Simpanan/LPS) was established by the Government to guarantee the deposits of depositors, maintain the stability of the banking system in accordance with its authority, protect depositor funds, and resolve or handle failed banks. The responsibility of LPS as a guarantor is to pay guarantee claims for the deposits of customers of banks whose business licenses have been revoked and to appoint a liquidation team to settle the assets and liabilities of those banks. LPS also actively maintains the stability of the banking system through rescue or recovery efforts for failed banks, both those without systemic impact and those with systemic impact. In rescuing failed banks, LPS has several authorities, including taking over and exercising all rights and powers of shareholders, including the General Meeting of Shareholders (GMS); controlling, managing, selling, or transferring bank assets; conducting temporary capital participation; and transferring management to other parties